2015
DOI: 10.1007/s00251-015-0834-5
|View full text |Cite
|
Sign up to set email alerts
|

Differences in genetic variation in antigen-processing machinery components and association with cervical carcinoma risk in two Indonesian populations

Abstract: Genetic variation of antigen-processing machinery (APM) components has been shown to be associated with cervical carcinoma risk and outcome in a genetically homogeneous Dutch population. However, the role of APM component single nucleotide polymorphisms (SNPs) in genetically heterogeneous populations with different distributions of human papillomavirus (HPV) subtypes remains unclear. Eleven non-synonymous, coding SNPs in the TAP1, TAP2, LMP2, LMP7 and ERAP1 genes were genotyped in cervical carcinoma patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 29 publications
2
21
0
1
Order By: Relevance
“…Single nucleotide polymorphisms in ERAP1 have been associated with poorer prognosis and greater disease progression in human papillomavirus‐positive cervical carcinoma . A combination of SNP in ERAP1, TAP2 and LMP7 is associated with an increased risk of developing cervical carcinoma . In addition, the presence of a homozygous ERAP1 haplotype (ERAP1‐56 major and ERAP‐127 minor) correlates with a significantly worse overall survival, highlighting ERAP1 as an independent predictor of survival .…”
Section: Mhc Class I Antigen Processing and Presentation In Tumour Immentioning
confidence: 99%
“…Single nucleotide polymorphisms in ERAP1 have been associated with poorer prognosis and greater disease progression in human papillomavirus‐positive cervical carcinoma . A combination of SNP in ERAP1, TAP2 and LMP7 is associated with an increased risk of developing cervical carcinoma . In addition, the presence of a homozygous ERAP1 haplotype (ERAP1‐56 major and ERAP‐127 minor) correlates with a significantly worse overall survival, highlighting ERAP1 as an independent predictor of survival .…”
Section: Mhc Class I Antigen Processing and Presentation In Tumour Immentioning
confidence: 99%
“…To date, over 30 genes have been studied for their role in cervical cancer risk and these include, Bid, BRIP1, Caspase 8, CCR2, CTLA4, CYP1A1, EXO1, FASLG, FASR, HOTAIR, IFN gamma, PARP1, XRCC1, MDM2, IL10, IL12, HLA B/C, MTHFR, Tap2, TNF-a, TLR9, p16, PIK3CA, p21, and p53 Martínez-Nava et al, 2016;Mehta et al, 2015;Mei et al, 2014;Dos Santos et al, 2016;Sousa et al, 2011;Tsakogiannis et al, 2017;and Wang et al, 2017). Of these, genes only nine have been researched in African populations, highlighting a big gap in cervical cancer molecular epidemiology studies in a continent where 90% of the cervical cancer-related deaths are predicted (MboubaBouassa et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Current reports show the involvement of Caspase 8, CCR2, CTLA4, CYP1A1, EXO1, FASLG, FASR, HOTAIR, IFN gamma, PARP1, XRCC1, MDM2, IL10, IL12, HLA B/C, MTHFR, Tap2, TNF-a, TLR9, p16, PIK3CA, and p21 in cervical susceptibility (Alanazi et al, 2013;Barbisan et al, 2012;Chang et al, 2015;Jin et al, 2017;Ma et al, 2013;Martínez-Nava et al, 2016;Mehta et al, 2015;Mei et al, 2014;Piccolo and Crispi, 2012;Roszack et al, 2014;Dos Santos et al, 2016;Sousa et al, 2011;Tsakogiannis et al, 2017;Wang et al, 2017;and Zhuo et al, 2014). However, these findings have mostly been corroborated in Caucasian and Asian populations, and only a few have been reported on African populations.…”
Section: Genetics and Cervical Cancermentioning
confidence: 99%
“…To further investigate the contribution of genetic variations in the APM to HPV-induced cervical carcinoma risk, A.M Mehta et al in 2015 conducted a further study on the genotype and genotype interactions of 11 previously identified SNPs in seven genes coding for some APM components, including ERAP1 [86]. The analysis was based on the occurrence of these variants in Javanese and Balinese Indonesian populations, in whom HPV is almost endemic [87].…”
Section: Eraps and Human Papilloma Virus (Hpv)mentioning
confidence: 99%